Studi Kelayakan Usaha Media Sosial Instagram Tentang Edukasi Kesehatan Gigi dan Mulut - Dwinanda, Jessica Sukma; Laut, Deru Marah; Widyastuti, Tri; Chaerudin, Denden Ridwan (Jurnal Terapi Gigi dan Mulut, 2024)
Oral health is influenced by genes, behavior, environment, and oral care. Behavior is a major factor in high oral health problems. Behavior is influenced by knowledge. Oral health education that can be done through social media is one way to increase knowledge. Instagram social media is one of the most popular platforms in Indonesia so that it has a business opportunity to be used as an oral health education platform and can be used as a learning medium in increasing knowledge. This study aims to determine the feasibility of an Instagram social media business on oral health education based on aspects of a business feasibility study. This method approach taken is descriptive qualitative research. Data collection procedures in this study were carried out through distributing g-forms to Instagram social media followers and in-depth interviews with entrepreneurship experts, material experts, and media experts. The results showed that the Instagram social media business on oral health education was declared feasible based on 5 aspects of the business feasibility study, namely market and marketing, technical and technological, operational management, economic and financial, and juridical. So it can be concluded that Instagram social media is worthy of being an entrepreneur in the field of oral health education.